2018
DOI: 10.21767/amj.2018.3399
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of trauma-focused cognitive-behavioural therapy in the treatment of depression of divorced women

Abstract: Background Divorce and disintegration of the family centre is a social problem having consequences considered as the main problems of current societies. Aims Therefore, the aim of this study was to determine the effectiveness of trauma-based cognitive-behavioural therapy in the treatment of depressed divorced women. Methods Materials and Methods: The experimental method was a pretest-posttest design control group with a three-month follow up. The statistical population of this study was a total of 103 women wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Table 1 summarizes the main characteristics of the 32 unique studies included in the review, with one companion article [16] for a study which was later reported with a more thorough examination of findings [17] totaling 33 articles. More than half (n = 19) of the 32 studies were RCTs [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] whereas twelve studies were quasi-experimental [36][37][38][39][40][41][42][43][44][45][46][47] and one was retrospective study [48]. Thirteen studies were conducted in the U.S. [17][18][19]22,26,27,29,35,[39][40][41]45,47]; five in the Netherlands …”
Section: Overview Of Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 1 summarizes the main characteristics of the 32 unique studies included in the review, with one companion article [16] for a study which was later reported with a more thorough examination of findings [17] totaling 33 articles. More than half (n = 19) of the 32 studies were RCTs [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] whereas twelve studies were quasi-experimental [36][37][38][39][40][41][42][43][44][45][46][47] and one was retrospective study [48]. Thirteen studies were conducted in the U.S. [17][18][19]22,26,27,29,35,[39][40][41]45,47]; five in the Netherlands …”
Section: Overview Of Studiesmentioning
confidence: 99%
“…The average sample size was 78 participants, with a range from 10 participants [38] to 297 participants [48]. Of the studies included, 67% had a sample size above 50 [18][19][20][21][22]26,[29][30][31][32][33][34]36,37,[39][40][41][42][46][47][48].…”
Section: Overview Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations